Due diligence in the characterization of matrix effects in a total IL-13 Singulex™ method. (April 2014) - Fraser, Stephanie; Soderstrom, Catherine
After obtaining her PhD in Cellular and Molecular biology from the University of Nevada, Reno, Stephanie has spent the last 15 years in the field of bioanalysis. She has held positions in academia, biotech, contract research and large pharma where she has managed ligand binding assay (discovery to Phase IIb clinical) and flow cytometry (preclinical) laboratories as well as taken the lead on implementing new/emergent technologies. Currently Stephanie leads Pfizer's Regulated Bioanalysis Ligand Binding Assay group, focusing on early clinical biomarker support. Interleukin (IL)-13, a Th2 cytokine, drives a range of physiological responses associated with the induction of allergic airway diseases and inflammatory bowel diseases. Analysis of IL-13 as a biomarker has provided insight into its role in disease mechanisms and progression. Serum IL-13 concentrations are often too low to be measured by standard enzyme-linked immunosorbent assay techniques, necessitating the implementation of a highly sensitive assay. Previously, the validation of a Singulex™ Erenna ® assay for the quantitation of IL-13 was reported. Herein we describe refinement of this validation; defining the impact of matrix interference on the lower limit of quantification, adding spiked matrix QC samples, and extending endogenous IL-13 stability. A fit-for-purpose validation was conducted and the assay was used to support a Phase II clinical trial.